Vi(c)toria octavi l(iberta) occisa est.: Un nuevo epígrafe romano de chillón (Ciudad Real. Conventus Cordubensis, Baetica) - Abascal Palazón, Juan Manuel, 1958- (2023)
Una inscripción romana descubierta en Chillón (Ciudad Real) contiene una nueva evidencia del uso del verbo occido para indicar la muerte violenta de una persona. El testimonio procede de un área rural en el territorio de Sisapo y constituye uno de los testimonios epigráficos del extremo occidental de la provincia de Ciudad Real
A Roman inscription near discovered in Chillón (Ciudad Real) contains a new evidence of the Latin verb occido to indicate the violent death of a person. The testimony comes from a rural area in the territory of Sisapo and constitutes one of the few epigraphic evidence from the extreme west of Ciudad Real.
Keywords: Epigramas latinos